A little respect: four case studies of HCI’s disregard for other disciplines - Marshall, Joe; Linehan, Conor; Spence, Jocelyn; Rennick-Egglestone, Stefan (2017)
HCI research often demonstrates lack of respect for other disciplines, evidenced by the way work from those disciplines are cited in CHI papers. We present 4 case studies that demonstrate; 1) that HCI researchers sometimes misunderstand and misrepresent work from other disciplines, and 2) how initial misrepresentations can become ‘accepted wisdom ’within HCI. This disregard for other disciplines leads to errors such as authors citing work to support ‘facts’ precisely opposite to those demonstrated by the cited literature. We conclude with recommendations for authors, editors, publishers and readers on how to reduce the risk of such failures.